1851 Cal. Stat. 360-61 - (:unkn) unknown (My University, 1851)
An Act to Reincorporate the City of San Francisco, § 13: Granted the city of San Francisco authority to regulate houses for the storage of gun-powder and other combustibles.
Keywords: GUNPOWDER - STORAGE